The digital endorser: how do virtual influencers impact destination brand engagement? / Xinying Yuan and Faiz Izwan Anuar - Xinying, Yuan; Anuar, Faiz Izwan (Faculty of Hotel & Tourism Management, Universiti Teknologi MARA, 2024)
This research investigates the influence of virtual influencers on brand engagement and travel intentions towards Chinese tourism destinations. Utilizing the Partial Least Squares Structural Equation Modelling (PLS-SEM) methodology, we explored the extent to which content credibility and interaction quality of virtual influencers impact destination brand engagement and subsequent tourist intentions, contextualizing these effects within the framework of parasocial relationship theory. Drawing from a sample of 201 Chinese tourism social media enthusiasts, the findings reveal that neither interaction quality nor content credibility exert a direct influence on destination brand engagement. Instead, parasocial relationships emerge as a pivotal mediator in this nexus. This investigation bridges the existing knowledge chasm between the realm of virtual influencers and the theory of parasocial relationships, offering invaluable insights for tourism destination entities aiming to leverage virtual influencers for heightened tourist attraction and brand engagement. Additionally, the insights derived from this study bear profound implications for the refinement of digital marketing strategies and the evolution of future tourism market dynamics.